О некоторых новых типах газетньvс заголовков (на материалe прессы 80-90-х годов) - НИКАБАДЗЕ, ЛИАНА У. (Stylistyka, 2021)
In Russian press one can observe а tendency to enrich the types of headlines, including ones of complex semantics. There appear, more and more frequently, puzzle-like headlines, in which the rules of syntactic and semantic coherence are violated, or which require complex interpretation rules (like deciphering metaphors, metonymies and distorted formulas).Colloquial language in the system of the Russian literary language and colloquiality in the history of the Russian artistic language.